Tree abundance and elevation influence the occurrence of limestone hill forest-dwelling stump-tailed macaques (Macaca arctoides) in northern Peninsular Malaysia - Sulai, Petra; Ling, Tee Sze; Ghazali, Amal; Syamil, Abd Rahman; Amran, Afiq; Lechner, Alex; Md Sharif, Badrul Azhar (Elsevier, 2025)
Stump-tailed macaques (Macaca arctoides) are difficult to study in the tropical rainforests because of lack of visibility and thus little is known about their ecology. Stump-tailed macaque may be at greater risk of local extinction than other macaque species in Peninsular Malaysia, but baseline data on their population status in forest habitat are lacking. This study attempts to evaluate the habitat needs of the stump-tailed macaque in a forest reserve that is not among the Peninsular Malaysia's primary protected areas (such as national parks and wildlife reserves). We examined the ecological relationship between stump-tailed macaque encounters and site-level habitat and vegetation characteristics. We also estimated the site occupancy of stump-tailed macaques and identified the habitat and vegetation characteristics that determine its detection probability. Our findings suggest that stump-tailed macaques prefer habitats with more trees with Diameter at Breast Height (DBH) ≥ 50 cm, fewer trees with DBH ≤ 50 cm, and lower elevation. However, the detection probability of the macaque species was positively related to the elevation. Although stump-tailed macaques are not exclusively arboreal, they nonetheless require forest habitats with an abundance of trees to facilitate population dispersal and animal movement. Our findings suggest that although stump-tailed macaques are restricted to the undisturbed limestone hill forest, they select certain tree size attributes within the forest, indicating that not all undisturbed habitat condition is of equal value for the stump-tailed macaque populations. Ecological requirements within these habitats need to be discerned for the long-term population viability. The findings highlight the importance of conserving forests with a good number of large trees and a diverse tree size structure, particularly at lower elevations, to maintain healthy macaque populations. Conservation strategies should include long-term monitoring on the stump-tailed macaque populations and preventing habitat loss and vegetation clearing.